Soil erosion rates in rangelands of northeastern Patagonia: A dendrogeomorphological analysis using exposed shrub roots - Chartier, Marcelo Pablo (2009)
Soil erosion is an important process of land degradation in many rangelands and a significant driver of desertification in the world's drylands. Dendrogeomorphology is an alternative to traditional methods for determining soil erosion rate. Specifically, the vertical distance between the upper portion of exposed roots and the actual soil surface can be used as a bioindicator of erosion since plant establishment. In this study, we determined (i) the soil erosion rate from exposed roots of the dwarf shrub Margyricarpus pinnatus [Lam.] Kuntze in two ecological sites in the northeastern rangelands of Patagonia and (ii) the relationship between shrub age and upper root diameter. We selected two ecological sites, a pediment-like plateau and a flank pediment, where the dominant soils were Xeric Haplocalcids and Xeric Calciargids, respectively. The soil erosion rates in the pediment-like plateau and in the flank pediment were 2.4 and 3.1 mm yr- 1, respectively. Data clearly indicate a high rate of soil erosion during the mean 8-year life span of the dwarf shrubs in degraded patches, which represent ~ 10% of surface cover in the study area. Simple linear regression analysis yielded a highly significant predictive model for age estimation of M. pinnatus plants using the upper root diameter as a predictor variable. The measurement of ground lowering against datable exposed roots represents a simple method for the determination of soil erosion rates. In combination with other soil surface features, it was used to infer the episodic nature of soil erosion. This approach could be particularly useful for monitoring the effects of land management practices on recent soil erosion and for the establishment of records in regions where historical data regarding this process are scarce or absent.